Facial Mobility after Maxilla-Mandibular Advancement in Patients with Severe Obstructive Sleep Apnea Syndrome: A Three-Dimensional Study - Laura Verzé; Francesca Antonella Bianchi; Niccolò Barla; Serena Maria Curti; Giovanni Gerbino; Guglielmo Amedeo Ramieri (International Journal of Dentistry)
Introduction. The functional results of surgery in terms of facial mobility are key elements in the treatment of patients. Little is actually known about changes in facial mobility following surgical treatment with maxillomandibular advancement (MMA). Objectives. The three-dimensional (3D) methods study of basic facial movements in typical OSAS patients treated with MMA was the topic of the present research. Materials and Methods. Ten patients affected by severe obstructive sleep apnea syndrome (OSAS) were engaged for the study. Their facial surface data was acquired using a 3D laser scanner one week before (T1) and 12 months after (T2) orthognathic surgery. The facial movements were frowning, grimace, smiling, and lip purse. They were described in terms of surface and landmark displacements (mm). The mean landmark displacement was calculated for right and left sides of the face, at T1 and at T2. Results. One year after surgery, facial movements were similar to presurgical registrations. No modifications of symmetry were present. Conclusions. Despite the skeletal maxilla-mandible expansion, orthognathic surgical treatment (MMA) of OSAS patients does not seem to modify facial mobility. Only an enhancement of amplitude in smiling and knitting brows was observed. These results could have reliable medical and surgical applications.